2002
DOI: 10.1002/glia.10159
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted multipotential neural precursor cells migrate into the inflamed white matter in response to experimental autoimmune encephalomyelitis

Abstract: Transplanted neural precursor cells remyelinate efficiently acutely demyelinated focal lesions. However, the clinical value of cell transplantation in a chronic, multifocal disease like multiple sclerosis will depend on the ability of transplanted cells to migrate to the multiple disease foci in the brain. Here, we expanded newborn rat neural precursor cells in spheres and transplanted them intracerebroventricularly or intrathecally in rats. The cells were labeled by the nuclear fluorescent dye Hoechst or by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
1
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(199 citation statements)
references
References 39 publications
12
174
1
12
Order By: Relevance
“…27 Isolation of neural precursors and growth of neurospheres. This procedure is based on the studies of Ben-Hur et al 28,29 For the derivation of neural progenitors, newborn (PN1-PN2) HS/Ibg mice were used. Cerebral cortices were minced, digested in 0.025% trypsin for 20 min and dissociated with a 5 ml Sphere transplantation.…”
Section: Specific Methodsmentioning
confidence: 99%
“…27 Isolation of neural precursors and growth of neurospheres. This procedure is based on the studies of Ben-Hur et al 28,29 For the derivation of neural progenitors, newborn (PN1-PN2) HS/Ibg mice were used. Cerebral cortices were minced, digested in 0.025% trypsin for 20 min and dissociated with a 5 ml Sphere transplantation.…”
Section: Specific Methodsmentioning
confidence: 99%
“…Recruitment and mobilization of OPCs and multipotential neural precursors in the models of MS have been mainly attributed to the inflammatory process. Brain inflammation attracts the migration of both endogenous [57] and transplanted [94][95][96][97] precursor cells. Various inflammatory cytokines can induce neural/oligodendrocyte precursor cell migration.…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%
“…Expression of PSA-NCAM on the cell membrane has been associated with stem cell commitment to neuronal or glial fate, depending on time and place in development [135][136][137]. Indeed, such PSA-NCAM+ glial precursors, growing as neurospheres and also termed as oligospheres [135,138], efficiently myelinated the brains of shi mice [138][139][140], remyelinated 95 to 100% of axons following local injection into the dorsal columns of rats [141], and efficiently migrated along inflamed white matter tracts of rats with EAE [94,95]. Similarly, adult human SVZ precursors remyelinated the adult rat spinal cord [142].…”
Section: Cell Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that stimulated neurogenesis occurs in the brains of rodent models of epilepsy, stroke, trauma, Alzheimer's, Parkinson's and Huntington's diseases (Parent, 2003). In demyelinating disease models, such as an experimental autoimmune encephalomyelitis (EAE), an animal model of MS, progenitors primarily form oligodendrocytes and remyelinate damaged white matter (Picard-Riera et al, 2002;Ben-Hur et al, 2003;Pluchino et al, 2003).…”
Section: Mechanisms Of Neurogenesismentioning
confidence: 99%